2008
DOI: 10.1002/chem.200701591
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Crystal Structure and Locating the Catalytic Activity of Micro‐ and Mesoporous ZSM‐5 Zeolite Crystals by Using In Situ Optical and Fluorescence Microscopy

Abstract: A combination of optical and fluorescence microscopy was used to study the morphology of micro‐ and mesoporous H‐ZSM‐5 zeolite crystals (17×4×4 μm) and to evaluate, in a spatially resolved manner, the effect of mesoporosity, introduced via desilication, on catalytic performance. For this purpose, the oligomerization of various styrene molecules was used as a model reaction, in which the carbocation intermediates formed in the zeolite pores act as reporter molecules. In situ confocal fluorescence measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 39 publications
(51 reference statements)
6
98
0
2
Order By: Relevance
“…More specifically, a band and a shoulder located at 610 nm and 640 nm, assigned to more conjugated linear carbocations. 19,21,28 When the oligomerization reaction is performed on H-ZSM-5-700, significant differences are observed in the UV-Vis absorption spectra, as shown in Fig. 1(c), where the intensities of the absorption bands at 610 nm and 640 nm drastically increase.…”
Section: Uv-vis Micro-spectroscopymentioning
confidence: 99%
“…More specifically, a band and a shoulder located at 610 nm and 640 nm, assigned to more conjugated linear carbocations. 19,21,28 When the oligomerization reaction is performed on H-ZSM-5-700, significant differences are observed in the UV-Vis absorption spectra, as shown in Fig. 1(c), where the intensities of the absorption bands at 610 nm and 640 nm drastically increase.…”
Section: Uv-vis Micro-spectroscopymentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Interestingly, the arrangement of these subunits, known as the internal architecture of a crystal, was found to be dependent not on the crystal framework type, but on the external morphology. For example, in the case of large MFI crystals (i.e., ZSM-5 and silicalite molecular sieves) it was found that four related but distinct intergrowth structures exist depending on the length/width (L/W) aspect ratios of the crystals.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8] These spectroscopic methods have proven to be very successful in elucidating valuable structure-function relationships for acid-base catalytic reactions. In the work of Roeffaers et al fluorescence microscopy has been applied to demonstrate the crystal-face-dependent catalysis on layered double hydroxide (LDH) materials.…”
mentioning
confidence: 99%